Sustainable transport solutions low carbon buses in the People Republic of China. (Metro Manila, Philippines Asian Development Bank, 2018)
This publication discusses the real world performance data of low carbon buses in the People Republic of China. It also reviews the environmental and financial impacts, as well as the policies used to promote them. The People Republic of China has taken the lead in the deployment of low carbon buses and is moving toward full electrification to address climate change and reduce greenhouse gas emissions. Data and information in this publication can benefit countries interested in promoting low-carbon buses to design appropriate support climate change policies.
Keywords: Sustainable transportation -- China; Electronic books